The Influence of Implementation of Free Learning Curriculum and Teacher's Role on Students' Character Building in Christian Religion and Moral Education Subjects at SMK Negeri 2 Loli, West Sumba Regency - Daku Wala, Gusta Bara; Tari*, Ezra; Ali, Umar (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
This study aims to determine the magnitude of the relationship and influence of the implementation of the independent learning curriculum and the role of the teacher on the formation of student character in the subject of Christian Religion and Moral Education (CREBP) at SMK Negeri 2 Loli, West Sumba Regency. The population in this study were class XI (eleven) students at SMK Negeri 2 Loli. The research sample was 62 students, taken by proportional random sampling technique. The collection of research data was carried out using a questionnaire method. While the data analysis is quantitative with descriptive statistical techniques. The results of this study are: (1) there is a positive and significant relationship between the implementation of the independent learning curriculum and the formation of student character.